(untitled) (Global Journal of Science Frontier Research, 2016)
Mushrooms are important fungi that play a great role for food self-sufficiency and to fill the gap of protein deficiency in most cereal crops, vegetables and fruits. Moreover, they are known for their flavor enhancing property, medicinal value a well as cholesterol free food. However, Mushroom production in Ethiopia is still less known due to multiple problems which include high input cost, lack of quality of spawn, lack of proper production skill, and lack of information on substrates. In view of this, the experiment was conducted at Arsi University, College of Agriculture and Environmental Science during 2013/14 Cropping years with the objectives of evaluating different organic substrates and pasteurized methods on Pleurotus ostreatus yield, biological efficiencies and nutritional values. Factorial combination of seven substrates (Dried faba bean stalk, Maize Stalk, Wheat straw, Teff straw, Eucalyptus Sawdust, Wheat straw + Teff straw+ Faba bean stalk and Saw dust + Faba bean stalk ) and two pasteurization methods (Cold water treatment and Hot water ) were used.